DNA vaccine against visceral leishmaniasis: a promising approach for prevention and control. (May 2016) - Kumar, A.; Samant, M.
Summary: The visceral leishmaniasis (VL) caused by Leishmania donovani parasite severely affects large populations in tropical and subtropical regions of the world. The arsenal of drugs available is limited, and resistance is common in clinical field isolates. Therefore, vaccines could be an important alternative for prevention against VL. Recently, some investigators advocated the protective efficacy of DNA vaccines, which induces the T cell‐based immunity against VL. The vaccine antigens are selected as conserved in various Leishmania species and provide a viable strategy for DNA vaccine development. Our understanding for DNA vaccine development against VL is not enough and much technological advancement is required. Improved formulations and methods of delivery are required, which increase the uptake of DNA vaccine by cells; optimization of vaccine vectors/encoded antigens to augment and direct the host immune response in VL. Despite the many genes identified as vaccine candidates, the disappointing potency of the DNA vaccines in VL underscores the challenges encountered in the efforts to translate efficacy in preclinical models into clinical realities. This review will provide a brief background of DNA vaccines including the insights gained about the design, strategy, safety issues, varied candidates, progress and challenges that play a role in their ability against VL.